2-Hydrazinoquinoline: A Reactive Matrix for Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry to Detect Gaseous Carbonyl Compounds. Issue 2 (April 2016) - Shigeri, Yasushi; Kamimura, Takuya; Ando, Masanori; Uegaki, Koichi; Sato, Hiroaki; Tani, Fumito; Arakawa, Ryuichi; Kinumi, Tomoya
The sensitivity, range of applications, and reaction mechanism of 2-hydrazinoquinoline as a reactive matrix for matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) were examined. Using a reaction chamber (125 L) equipped with a stirring fan and a window for moving the MALDI-MS plate and volatile samples in and out, the sensitivities of 2-hydrazinoquinoline to gaseous aldehydes (formaldehyde, acetaldehyde, propionaldehyde, and n -butyraldehyde) and ketones (acetone, methyl ethyl ketone, and methyl isobutyl ketone) were determined to be at least parts per million (ppm) levels. On the other hand, carboxylic acids (formic acid, acetic acid, propionic acid, and butyric acid) and esters (ethyl acetate, pentyl acetate, isoamyl acetate, and methyl salicylate) could not be detected by 2-hydrazinoquinoline in MALDI-MS. In addition to 2, 4-dinitrophenylhydrazine, a common derivatization reagent for analyzing carbonyl compounds quantitatively in gas chromatography and liquid chromatography, the dissolution of 2-hydrazinoquinoline in an acidic solution, such as trifluoroacetic acid, was essential for its function as a reactive matrix for MALDI-MS.